Epidemiological analysis of maternal hypertensive disorders of pregnancy - Aijuan Yuan; Hui Huang (Frontiers in Medicine)
BackgroundWe aimed to provide a comprehensive overview of the epidemiology of hypertensive disorders of pregnancy (HDP) from 1990 to 2021, examining incidence and trends across national, continental, and global levels.MethodsHDP were assessed by calculating the age-standardized incidence rate (ASIR), age-standardized disability-adjusted life years (DALYs) rate, and the estimated annual percentage change (EAPC) for each region and country. The Global Burden of Disease (GBD) 2021 Study age-standardized rates, which were obtained from 204 countries and territories, were used to analyze the burden based on age and sociodemographic index (SDI).ResultsThe global burden of HDP has changed substantially between 1990 and 2021. The total number of DALYs was 2.47 million (95% UI: 2.08 to 2.96), and the ASIR was 461.94 per 100,000 in 2021. The estimated annual percentage change (EAPC) for the DALY rate was −2.10 (95% CI: −2.15 to −2.04), and the EAPC for ASIR was −0.51 (95% CI: −0.56 to −0.45). The Russian Federation, Romania, and Georgia had the greatest increases in ASIR over time. Guam, American Samoa, and the United Republic of Tanzania had the highest EAPC for the DALY rate. Analysis by age showed that maternal hypertensive disorders caused the highest DALYs among women aged 25–39 years and the lowest DALYs among those aged 50–54 years. There was a positive relationship between ASIR and SDI. The same trend was observed for the DALY rate.ConclusionOur findings revealed that DALY rates and incidence rates of HDP decreased in most regions, except in areas with lower sociodemographic indices, such as the Caribbean. The greatest burden of HDP was observed among women aged 25–39 years. These results underscore the need for targeted interventions in low-SDI regions and highlight the importance of addressing HDP as a key component of maternal health initiatives globally.